2023
DOI: 10.1021/acs.jpcc.2c06625
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Analysis of Reaction Parameters in UV-Mediated Synthesis of Gold Nanoparticles

Abstract: Gold nanoparticles represent an important class of functional nanomaterials for optoelectronics, biomedical applications, and catalysis. Therefore, controllable synthesis of nanoparticles with specified size and shape is important. Though reduction of gold ions is quite a simple process and may be performed with many different protocols, the reproducibility of the results and transfer of protocols between independent research groups remains a challenging task. Machine learning analysis based on statistical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…XGBoost [97] IR and Raman spectra Predict surface-adsorbate interaction properties ET, [98] SISSO [98] Synthesis Selected synthesis descriptors Classify selected features of spectra ET [99] The citrate to gold (III) ratio, scanning velocity and radiation intensity Predict nanoparticle size ANN [ 100] Spectroscopic characteristics based on UV-vis/DLS Optimize experimental/reaction conditions GA, [ 101] BO+DNN [ 102] Reaction conditions Predict selected spectroscopic characteristics of nanoparticles SVR [103] Target molecules Propose a sequence of chemically viable reaction steps ANN [ 104] Instrumentations and spectral preprocessing Complex 2D images Optimize illumination light source parameters CNN [ 105] Patterns of weakly scattering perturbations Design transmission matrices VAE [ 106] Scattering spectra of nanostructures Encode up to 9 bits of information for high-density optical information storage CNN [ 107] Noisy Raman spectra Remove the baseline, cosmic rays, and noise simultaneously or separately CNN, [108][109][110] ResNet, [ 111] U-net, [ 111] ANN+U-net, [ 112] PCA, [113] GAN [ 114] Spectral analysis SERS spectrum Identify the existence of the molecular fingerprints…”
Section: Molecular Graphmentioning
confidence: 99%
See 3 more Smart Citations
“…XGBoost [97] IR and Raman spectra Predict surface-adsorbate interaction properties ET, [98] SISSO [98] Synthesis Selected synthesis descriptors Classify selected features of spectra ET [99] The citrate to gold (III) ratio, scanning velocity and radiation intensity Predict nanoparticle size ANN [ 100] Spectroscopic characteristics based on UV-vis/DLS Optimize experimental/reaction conditions GA, [ 101] BO+DNN [ 102] Reaction conditions Predict selected spectroscopic characteristics of nanoparticles SVR [103] Target molecules Propose a sequence of chemically viable reaction steps ANN [ 104] Instrumentations and spectral preprocessing Complex 2D images Optimize illumination light source parameters CNN [ 105] Patterns of weakly scattering perturbations Design transmission matrices VAE [ 106] Scattering spectra of nanostructures Encode up to 9 bits of information for high-density optical information storage CNN [ 107] Noisy Raman spectra Remove the baseline, cosmic rays, and noise simultaneously or separately CNN, [108][109][110] ResNet, [ 111] U-net, [ 111] ANN+U-net, [ 112] PCA, [113] GAN [ 114] Spectral analysis SERS spectrum Identify the existence of the molecular fingerprints…”
Section: Molecular Graphmentioning
confidence: 99%
“…Specifically, a lot of faults are absent from the reported results and some details might even be consciously or unconsciously left out. [99,241] However, database consisting of comprehensive facts from systematic experiments is critical for the AI-based optimization. Therefore, microfluidic systems have been regarded as an excellent alternative to produce training data because the parameters are easy to control and it can do experiments with minimal volumes in a highly efficient manner [242] (Figure 4a).…”
Section: Ai-instructed Synthesis Substrates and Reportersmentioning
confidence: 99%
See 2 more Smart Citations
“…60 Guda et al demonstrated 3D printed module devices for gold nanoparticle synthesis. 61 Microfluidic technologies have gained significant popularity in the field of organic synthesis and catalysis. 62 The production of various o-disubstituted benzenes in a continuous flow regime, 62 screening applications of diazomethane, 63 and anaerobic catalytic oxidation of stilbenes 64 are examples.…”
Section: Introductionmentioning
confidence: 99%